THE USE OF BAMBOO DANCING TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILL - Eva Mahmudah (English Education Department Slamet Riyadi University Surakarta, 2020)
EnglishZis a globalZlanguage whichZis very importantZin this world. It consisted of four skillZwhich needed byZthe studentsZespecially speakingZskill. Students need that skill toZcommunicate withZother peopleZaround the world. It alsoZcan improveZthe students’ ability in English. But, thereZwere soZmany problemsZin studentsZespecially in students’Zspeaking skill. This study aimed to find out whetherZBamboo DancingZTechnique canZimprove students’ speakingZskill and toZdescribe howZBamboo DancingZTechnique implemented in XI IPA 2 of MAN 1 Surakarta in 2019/2020 Academic Year. The method of the study wasZclassroom action research. ItZconsisted ofZtwo cyclesZincluding theZsteps of classroomZaction research. There wereZplanning, implementing, observing, andZreflecting. The test thatZused in thisZstudy was oralZtest and non–testZto collectZthe data. TheZnon-test wereZobservation, interview, and documentation. The result of this study showed that there was an improvement by implementing Bamboo DancingZTechnique to improveZstudents’ speaking skill. The mean score of pre-test was 55,86. Meanwhile in theZpost-test 1 in cycle 1, it improved to 65,29. In theZpost – test 2 the scoreZhad improved to 81. It canZbe concludedZthat BambooZDancing TechniqueZwas appropriate to improveZstudents’ speaking skill. Keywords: ClassroomZActionZReseach, BambooZDancing Technique, Speaking Skill.